SYNERGISTIC EFFECT OF ANTIBIOTICS AND MEDICINAL PLANTS AGAINST VIBRIO SPECIES ISOLATED FROM SHRIMP OF NATURAL WATERS AND COMMERCIAL AQUA PONDS - Dr. B. Nageshwari, Dr Maqsood Ahmed Mohammad, Kandrakunta Babu, K. Subhashini Devi, Dr. T. Sujatha, K. Durgarao (South Eastern European Journal of Public Health, 2025)
Shrimp aquaculture is a vital global industry that faces significant challenges due to Vibrio species infections, resulting in substantial economic losses. Vibrio parahaemolyticus, Vibrio cholerae, and Vibrio vulnificus are the pathogenic bacteria listed above, which cause vibriosis and reduce shrimp yield and quality. Disease control with antibiotics has led to antibiotic resistances causing conventional treatments to become less effective. As a result, it is imperative to develop available alternative therapy for controlling Vibrio infections in shrimp farming sustainably. This study evaluates the synergistic effect of selected antibiotics and medicinal plant extracts against Vibrio species from shrimp obtained from natural water and commercial aquaculture ponds. To determine bacterial resistance patterns, antimicrobial susceptibility testing was conducted to test for antimicrobial pattern and in the checkerboard assays to assess interactions of the plant extract & antibiotic. The findings indicate that for some combinations of antibiotics and bioactive compounds derived from plants, the resulting antibiotic efficiency is enhanced, the amount of required antibiotics can be reduced, and resistance development can be suppressed. These results demonstrate the feasibility of joining natural antimicrobial agents with treatment regimens, paving the way for improved disease management strategies in sustainable aquaculture.